The Goldsmith's Daughter - Landman, Tanya (Somerville, MA : Candlewick Press, 2009)
In the golden city of Tenochtitilan, the people live in awe of Emperor Montezuma and in fear of blood-hungry gods. Under an ill-fated sky, a girl is born, facing a life of submission and domestic drudgery. But Itacate has a secret passion of goldwork, forbidden to women, and is forced to disguise her identity to protect herself and her family. When her city is shaken by Cortez's invasion, Itacate challenges fate, culture, and faith by crafting golden statues and pursuing the love of a man who should be her enemy.
Includes bibliographical references.
Keywords: Aztecs -- Juvenile fiction; Aztecs -- Fiction; Indians of Mexico -- Fiction; Mexico -- History -- Conquest, 1519-1540 -- Fiction